Association between gestational weight gain and perinatal outcomes among twin gestations based on the 2009 Institute of Medicine (IOM) guidelines: a systematic review. (12th December 2022) - Lin, Dongxin; Huang, Zheng; Fan, Dazhi; Chen, Gengdong; Ye, Shaoxin; Wu, Shuzhen; Guo, Xiaoling; Luo, Caihong; Liu, Zhengping
Abstract: Background: Gestational weight gain (GWG) has been understudied among twin pregnancies. This systematic review aimed to review the data on the associations between GWG, based on the 2009 Institute of Medicine (IOM) guidelines and pregnancy outcomes among twin gestations. Methods: A systematic review was performed according to the PRISMA guidelines. A search for eligible studies published from January 2010 to August 2020 was conducted in the EMBASE, PubMed, Web of Science, ScienceDirect, and Cochrane databases. The methodological quality of the included studies was assessed using the Newcastle–Ottawa Scale. Data on study characteristics and main findings were extracted independently by two reviewers using a standard form. Outcomes of interest included (spontaneous) preterm birth (PTB), gestational hypertensive disorder (gestational hypertension and eclampsia), and small for gestational age (SGA). Results: Eighteen observational studies of twin gestations met the inclusion criteria. GWG below the IOM recommendations was reported to be associated with increased PTB and SGA while GWG above the recommendation was associated with increased gestational hypertensive disorder. However, the results were inconsistent. Methodological limitations, such as a retrospective design, the use of weekly GWG, a small sample size and insufficient adjustment, impeded the clarification of the association between GWG and perinatal outcomes. In addition, the optimal GWG for underweight women was not fully studied. Conclusions: The maintenance of weight gain within the 2009 IOM guidelines would decrease the risks of adverse outcomes among twin pregnancies. However, rigorous studies are warranted to provide robust evidence to refine the optimal GWG among twin gestations.